Class I PI3 kinase inhibition by the pyridinylfuranopyrimidine inhibitor PI-103 enhances tumor radiosensitivity - Prevo, Remko; Deutsch, Eric; Sampson, Oliver; Diplexcito, Julie; Cengel, Keith; Harper, Jane; O'Neill, Peter; McKenna, W Gillies; Patel, Sonal; Bernhard, Eric J (Cancer research (Chicago, Ill.), 2008)
Cell signaling initiated at the epidermal growth factor receptor (EGFR), RAS oncoproteins, or PI3K contributes to a common pathway that promotes tumor survival after radiation-induced DNA damage. Inhibition of signaling at the level of EGFR, RAS, and PI3K has been tested, but clinical applicability has been shown only at the level of the EGFR or by inhibiting RAS indirectly with prenyltransferase inhibitors. Inhibition of PI3K with LY294002 or wortmannin lacks specificity and has shown unacceptable toxicity in preclinical studies. We previously showed that inhibiting class I PI3K expression with siRNA resulted in enhanced radiation killing of tumor cells. Here, we tested the possibility of achieving specific tumor cell radiosensitization with a pharmacologic inhibitor of class I PI3K, the pyridinylfuranopyrimidine inhibitor PI-103. Our results show that inhibiting PI3K activity reduces phosphorylation of AKT at serine 473. Reduced survival is seen in cells with AKT activation and seems preferential for tumor cells over cells in which AKT activity is not elevated. Reduced survival is accompanied by persistence of DNA damage as evidenced by persistence of gamma H2AX and Rad 51 foci after irradiation in the presence of the inhibitor. Reduced survival does not result from cell cycle redistribution during the PI-103 treatment intervals tested, although combining PI-103 treatment with radiation enhances the G(2)-M delay observed after irradiation. These results indicate that pharmacologic inhibitors with enhanced specificity for class I PI3K may be of benefit when combined with radiotherapy.